2003
DOI: 10.1002/mds.10466
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb in multiple system atrophy

Abstract: Olfactory dysfunction is a characteristic clinical sign in Parkinson's disease (PD); it is also present in multiple system atrophy (MSA). The pathological basis of hyposmia or anosmia in PD is well known: the olfactory bulb (OB) contains numerous Lewy bodies and severe neuronal loss is present in the anterior olfactory nucleus (AON). We established that glial cytoplasmic inclusions (GCIs) are present in all the OBs from MSA cases. Their presence in the OB is diagnostic for MSA. Additionally, neuronal loss is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 22 publications
5
24
1
1
Order By: Relevance
“…Isolated GCI were detected In the olfactory bulb (Fig. 3a), consistent with previous reports [16]. The basal ganglia had mild neuronal loss and gliosis with iron pigment in the lateral putamen.…”
Section: Neuropathologic Findings (Case 2)supporting
confidence: 90%
“…Isolated GCI were detected In the olfactory bulb (Fig. 3a), consistent with previous reports [16]. The basal ganglia had mild neuronal loss and gliosis with iron pigment in the lateral putamen.…”
Section: Neuropathologic Findings (Case 2)supporting
confidence: 90%
“…Several studies have also suggested the lack of correlation between olfactory loss with duration or severity of the disease [27,29,30], which was confirmed by the present study. Studies that examined the correlation between pathological changes in the brain and results of olfactory tests suggested that olfactory dysfunction in MSA could be related to glial cytoplasmic inclusions in the olfactory bulb [31]. Another study examined the brain of patients with PSP at postmortem and identified neurofibrillary tangles and tau accumulation in the rhinencephalon, although only three of their patients had hyposmia [13].…”
Section: Discussionmentioning
confidence: 99%
“…In multiple system atrophy (MSA), glial cytoplasmatic inclusions may be present in the olfactory bulb [27,37]. However, most studies have found evidence of only a mild smell deficit [21,38,39,40 . ], and UPSIT scores are significantly higher than in PD [38].…”
Section: Multiple System Atrophymentioning
confidence: 99%